HUBUNGAN KADAR UREA SALIVA TERHADAP DERAJAT KEASAMAN (pH) SALIVA PADA ANAK USIA 12-15 TAHUN - Nifarea Anlila Vesthi; Grahita Aditya; Rizki Amalina (ODONTO : Dental Journal, 2015)
Introduction: One of the dental disease in the oral cavity that often experience by society are caries. Caries is one of the hard tooth tissue disease that can touch enamel, dentin, and sementum. One of the factor that affect caries process is saliva. Urea is one of the organic composition that compose saliva. Urea in salive plays as buffer capacity and the pH saliva adjustment.Methods: This study is an analytic observational with cross sectional approach, this study are conducted in Daarul 'Ilmi Islamic boarding school with 19 subject of 12-15 years old child. The data are obtained from the examination of urea saliva level and pH saliva in child. The level of urea saliva are measured using spectrophotometer tools and the pH saliva are measured using pH meter. The Shapiro-wilkare used to deterime the data normality, continue with Leuvenetest to determinde the data homogeneity data. Data are analyzed using Pearson test to determine the relation of urea level in saliva against the pH saliva.Results: According the data analysis, the data are in normal distribution and homogeneous. The research result are obtain average of urea level in urea sample is 13,45 mg/dl, and the average of pH saliva sampelis 7,15. The result of Pearsonstatistic testare obtain p value of = 0,000, with the positive correlation level of 0,902.Conclusion: The conclusion of this study are note that there are relation between the urea level in saliva against pH salive. This are proven from the Pearson test result with significance value of 0.000 (p< 0.05).